RETRACTED: Young plasma reverses anesthesia and surgery-induced cognitive impairment in aged rats by modulating hippocampal synaptic plasticity - Li, Yanan; Zhang, Qi; Yan, Wenyu; Wang, Xupeng; Yu, Jiaxu; Yin, Chunping; Zhou, Qi; Hou, Zhiyong; Wang, Qiujun (Frontiers in Aging Neuroscience, 2022)
We investigated the protective effect of young plasma on anesthesia- and surgery-induced cognitive impairment and the potential underlying mechanism using bioinformatics, functional enrichment analysis, gene set enrichment analysis, Golgi-Cox staining, dendritic spine analysis, immunofluorescence assay, western blot analysis, and transmission electron microscopy. Furthermore, we performed behavioral assessments using the open field test, the novel object recognition test, and the Morris water maze test. We identified 1969 differentially expressed genes induced by young plasma treatment, including 800 upregulated genes and 1169 downregulated genes, highlighting several enriched biological processes (signal release from synapse, postsynaptic density and neuron to neuron synapse). Anesthesia- and surgery-induced cognitive impairment in aged rats was comparatively less severe following young plasma preinfusion. In addition, the decreased levels of synapse-related and tyrosine kinase B/extracellular signal-regulated protein kinase/cyclic adenosine monophosphate response element-binding protein (TrkB/ERK/CREB) signaling pathway-related proteins, dendritic and spine deficits, and ultrastructural changes were ameliorated in aged mice following young plasma preinfusion. Together, these findings suggest that young plasma reverses anesthesia- and surgery-induced cognitive impairment in aged rats and that the mechanism is associated with the activation of the TrkB/ERK/CREB signaling pathway and improvement in hippocampal synaptic plasticity.